Fluorescent labeling of the root cap cells with the bioactive NBD-S chemical probe based on the cellulose biosynthesis inhibition herbicides - Tamogami, Shigeru (Biochem Biophys Rep, 2021)
Development of the methods to examine the molecular targets of biologically active compounds is one of the most important subjects in experimental biology/biochemistry. To evaluate the usability of the (7-nitro-2,1,3-benzoxadiazole)-thioether (NBD-S) probe for this purpose, bioactive chemical probe (1) as the cellulose biosynthesis (CB) inhibitor was synthesized and tested. As a result, a variety of fluorescently-labeled particles and organelles were found in the columella root cap cells of radish plants. Of note, well-defined cellular organelles were clearly recognized in the detaching root cap cells (border-like cells). These results imply that the bioactive NBD-S chemical probe could be a valuable direct-labeling reagent. Analysis of these fluorescent substances would be helpful in providing new information on defined molecular targets and events.